The Experimental Reconstruction of an Early Neolithic Underground Oven of Portonovo (Italy) - Cecilia Conati Barbaro; Vanessa Forte; Alberto Rossi (EXARC Journal)
This contribution presents the experimental reconstruction of an underground oven replicated according to the archaeological evidence unearthed from the Early Neolithic site of Portonovo-Fosso Fontanaccia (Ancona-Italy). A domed structure, measuring 190x180 cm diameter at the base and 50 cm in height, was dug in 15 hours, in a sediment compatible with the geological formation that features the archaeological site. The experimental protocol presented in this article aims to reconstruct techniques, timing and tools needed to dig the peculiar underground structures of Portonovo used by Neolithic groups and understand key topics regarding the entire technical process such as energy investment for the community, seasonality and lifespan.